ON THE CUSTOMS UNION OF BELARUS, KAZAKHSTAN AND RUSSIA - Simon, Jr, György (Economic Annals, 2010)
The article gives a general overview of the process of forming a customs union among three Soviet successor states – Belarus, Kazakhstan and Russia. Following some theoretical considerations, the author outlines the evolution of the idea of customs union within the CIS. Thereafter, he analyses the economic situation in its member states, with particular emphasis on their structural problems, economic efficiency and trade characteristics. He comes to the conclusion that the foregoing results have not helped diversify the economic structure of its participants and lessen their import dependence. Moreover, the declining level of intra-trade does not bode well for the future of this organisation, while the situation is further complicated by the negative impact of the present global crisis and increasing geopolitical rivalry in the region.